EVALUASI TINGKAT KESEHATAN KINERJA KEUANGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PALEMBANG - Yancik Syafitri (JURNAL KOMPETITIF, 2013)
The operational limits used in this study, including the financial performance of a PDAM the views of the main indicators consisting of: profitability, liquidity and solvency as well as additional indicators consisting of: Efficiency distribution, operating ratios and labor productivity. The purpose of this study was to obtain empirical evidence about the performance of the PDAM Palembang.This research was supported by quantitative research qualitative research. In the study has collected primary and secondary data. Primary data were obtained by means of unstructured interviews and semi-structured (unstructured and semistructured interviews) from Palembang city taps and secondary data obtained from financial statements.Research shows the level of financial performance and profitability during 2010 fluctuated 2008.2009. But above established guidelines. Similarly, liquidity and solvency, in other words, the financial performance of Palembang city taps into the healthy group. It is seen from the calculation of key indicators and additional indicators.Ã‚Â Key Word : Health Level Financial PerformanceÃ‚Â